Exercising the Role and Authority of Indonesia's Senate: Implications of Constitutional Court Decision 92/PUU-X/2012 - Kafandi, Muhammad Afif; Setiadi, Wicipto; Thohari, Ahmad Ahsin (LifeSciFi, 2024)
The Regional Representative Council (Dewan Perwakilan Daerah/DPD) in Indonesia is a legislative body that reflects the country's bicameral system, which includes two chambers. However, the DPD’s authority is notably weaker than that of the House of Representatives (Dewan Perwakilan Rakyat/DPR), leading to what is often described as